Labour market prognoses - trends, opportunities and limits - Bott, Peter [Verfasser]; Helmrich, Robert [Verfasser]; Schade, Hans-Joachim [Verfasser] (My University, 2009)
"The labour markets trends of tomorrow began yesterday. Past developments are being acted upon in order to make projections for the future. The dominant trend in terms of the supply of skilled workers is demographic development, whereas on the demand side the primary focus is on economic development. The aim of current labour market progress is to indicate which trends are currently most likely to loom large without necessarily being inevitable. Such prognoses constitute a concentrated point of focus for policy options. Where, however, do their opportunities and limits lie?" (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; G 2.3.4 Qualifikationswandel; Arbeitsmarktprognose; Demografischer Wandel; Erwerbspersonenpotenzial; Dienstleistungssektor; Höherqualifizierung; Qualifikationsbedarf; Qualifikationsanforderung; Wissensarbeit; Qualifikationswandel; Arbeitskräfteangebot; Bedarfsprognose; Qualifikationsnachfrage